2013
DOI: 10.1128/iai.01424-12
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Secretory Antibodies to Intestinal Mucosal Immunity against Helicobacter pylori

Abstract: dThe natural immune response to Helicobacter pylori neither clears infection nor prevents reinfection. However, the ability of secretory antibodies to influence the course of H. pylori infection has not been determined. We compared the natural progression of H. pylori infection in wild-type C57BL/6 mice with that in mice lacking the polymeric immunoglobulin receptor (pIgR) that is essential for the secretion of polymeric antibody across mucosal surfaces. H. pylori SS1-infected wild-type and pIgR knockout (KO) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 65 publications
0
18
0
2
Order By: Relevance
“…Finally, secretory antibodies can modulate the progress of H. pylori infection, particularly in the duodenum, as shown by Gorrell et al. : Knockout mice for polymeric immunoglobulin receptors had a very intense colonization of the duodenum .…”
Section: Helicobacter Pylori: Intestinal Manifestationsmentioning
confidence: 91%
See 1 more Smart Citation
“…Finally, secretory antibodies can modulate the progress of H. pylori infection, particularly in the duodenum, as shown by Gorrell et al. : Knockout mice for polymeric immunoglobulin receptors had a very intense colonization of the duodenum .…”
Section: Helicobacter Pylori: Intestinal Manifestationsmentioning
confidence: 91%
“…Even though a clear relationship could not be found, basic research demonstrated that H. pylori can use its pathogenic action against colonic cells, when they produce a gastric mucin (MUC5AC) [38]. Finally, secretory antibodies can modulate the progress of H. pylori infection, particularly in the duodenum, as shown by Gorrell et al: Knockout mice for polymeric immunoglobulin receptors had a very intense colonization of the duodenum [39].…”
Section: Helicobacter Pylori: Intestinal Manifestationsmentioning
confidence: 99%
“…A systematic analysis of studies on the role of breast-feeding in H. pylori infection has shown that breast-feeding can indeed protect against acquisition of new H. pylori infection, particularly in children in low-and middle-income countries (Chak et al, 2009). Further support for a protective role of SIgA antibodies came from a study showing that, whereas H. pylori infection in WT mice was spontaneously eradicated from the duodenum after three months, knockout mice lacking polymeric Ig receptor were abundantly colonized with H. pylori in the duodenum (Gorrell et al, 2013). Thus, H. pylori-specific SIgA antibodies may play a role in preventing acquisition of H. pylori infection by immune exclusion.…”
Section: Adaptive Immune Responsesmentioning
confidence: 95%
“…В некоторых исследованиях показано, что IgA содержится в желудочном соке большинства H. рylori инфицированных носителей, а в слюне этих пациентов выявлены sIgA. Предполагают, что наличие IgA в высоких титрах может говорить о повреждении эпителия слизистой желудка [26,27].…”
Section: Introductionunclassified